Using European funds for the purpose of practical learning the profession at the course in tourism services techniques at the John Paul II Salesian Sisters’ School in Suwałki - Kalejta, Joanna (Warsztaty z Geografii Turyzmu, 2017)
The policy of the European Union provides a wide access to education, in accordance with priorities. From the first Union financial perspective higher education has been widely discussed and highly funded. In this way, particularly children and young people have the opportunity to align educational differences and strengthen your professional path and a smooth entry into the labour market. Between 2007-2013 in the EU a special accent was put on the development of vocational education and training medium level, and higher. Now this trend is continued, in addition to the possibility. the mobility of students, that is, education on employers. This article presents three proprietary projects, implemented in the Salesian Comprehensive and Vocational School in Suwałki in the framework of European funding over the years 2010-2017.